Trade policy uncertainty and the WTO - Valeria Groppo; Roberta Piermartini (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
Do WTO commitments reduce the risk of trade policy reversals? To address this question, we rely on the theoretical model of varying cooperative tariffs by Bagwell and Staiger (1990) to specify our empirical model for the probability of a tariff increase. We then study how WTO tariff commitments affect this probability. We estimate our model using a database of WTO bound tariffs that we built for all WTO Members from 1996 to 2011 at the HS 6-digit level of disaggregation. Our results show that WTO commitments significantly reduce the probability of a tariff increase, even when the bound tariff is above the MFN applied rate. In addition, the WTO reduces trade policy uncertainty through its monitoring function. These results are robust to including political economy explanations of tariff changes and to addressing endogeneity concerns.
Keywords: F1; F5; 330; gains from trade agreements; commitments; tariffs formation; binding overhang